Gene therapy of neurodegenerative diseases: achievements, developments, and clinical implementation challenges - E. V. Melnikova; V. A. Merkulov; O. V. Merkulova (Биопрепараты: Профилактика, диагностика, лечение)
Neurodegenerative diseases (NDDs) are promising objects for the development of gene therapy products, primarily, due to the possible cause of these diseases (disruption of a gene or several genes), lack of effective therapy, and negative impact on the quality of life of both patients and their families and friends.The aim of the study was to identify trends and challenges in the development and preclinical and clinical studies of gene therapy products for NDDs and to analyse the international experience of expert assessment of the dossier for Zolgensma®, which received a conditional marketing authorisation.According to the analysis of the ongoing studies of gene therapy products for NDDs, the following major challenges arise at preclinical and clinical stages. For animal studies, a particular challenge is to select a disease model, a route of administration, and a target for effective gene therapy for polygenic disorders. For clinical trials, problematic aspects are the selection of a control group, the development of inclusion criteria for patients with a genetic variant that is an indication for a gene therapy product and exclusion criteria for patients with antibodies to this gene therapy product, the selection and justifi cation of a safe therapeutic dose since a gene therapy product can be administered to a patient only once, and the complexity of assessing clinical benefi ts of transgene expression in the human body due to the inaccessibility of brain tissue for analysis. Recent years have witnessed a breakthrough in gene therapy with the introduction of Zolgensma® (Novartis) to the world pharmaceutical market to treat children with spinal muscular atrophy type 1. The article analyses the experience of expert assessment of the marketing authorisation dossier for Zolgensma®, which can be used by drug developers bringing new medicines to the market of the Eurasian Economic Union under conditional marketing authorisation, which implies that the benefi ts of immediate patient access to these medicines will exceed the risks associated with incomplete data on their characteristics.